2020
DOI: 10.3126/njog.v15i1.29341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of endometrial histopathological patterns in Abnormal Uterine Bleeding

Abstract: Aims: To study the association of clinical profile of patients with Abnormal Uterine Bleeding with the different endometrial histopathological patterns Methods: A retrospective cross-sectional study was done in the department of Obstetrics and Gynaecology at a hospital in Karnataka, India from January 2017 to January 2019. Medical records were reviewed for all the cases of abnormal uterine bleeding who underwent endometrial biopsy. Results: There were 148 records of endometrial biopsies; &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…An earlier stage of presentation due to increase health awareness could explain high incidence in our study. 20 The incidence of endometrial hyperplasia in this study (5.11%) was less as compared to other studies as these patients may have been identified at a much earlier stage that is in the disordered proliferative phase. 19 Endometrial hyperplasia is a precursor of endometrial cancer.…”
Section: Resultscontrasting
confidence: 75%
“…An earlier stage of presentation due to increase health awareness could explain high incidence in our study. 20 The incidence of endometrial hyperplasia in this study (5.11%) was less as compared to other studies as these patients may have been identified at a much earlier stage that is in the disordered proliferative phase. 19 Endometrial hyperplasia is a precursor of endometrial cancer.…”
Section: Resultscontrasting
confidence: 75%
“…Additionally, parity wise distribution in this study noted multipara patients in three-fourths (75%), followed by primiparas (16%) and nulliparas (9%). Similarly, most of the patients were multipara in Choudhary and Nath 7 study (89%) and Singh et al 6 study (71.7%) and Chauhan et al 8 The present study delves into the varied complaints reported by patients, with menorrhagia being the most prevalent (80%), followed by polymenorrhagia (18%) and metrorrhagia (2%). Moreover, heavy bleeding was reported in 75% of cases and extremely heavy bleeding in 25%.…”
Section: Discussionsupporting
confidence: 54%
“…[17][18][19][20] The commonest myometrial lesion observed in present study were leiomyoma and majority of patients were in the range from 41-50 years age group (56.86%) which is in concordance with other studies done by Praseeda et al and Sapna et al where 33.5% and 55.0% respectively. 21,22 There are many minor factors or causes present AUB in the present study also but these are small number. These findings are in accordance to the many previous literature.…”
Section: Discussionmentioning
confidence: 67%